BRONCHIAL HYPERREACTIVITY AND BRONCHIAL ASTHMA DIFFERENTIAL DIAGNOSIS AND TREATMENTTHE SUPERVISOR (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article discusses the problems of differential diagnosis, diagnostic approaches, and treatment principles between bronchial hyperreactivity and bronchial asthma. Bronchial hyperreactivity is an oversensitivity of the bronchi in response to various factors, which can cause symptoms similar to bronchial asthma. Therefore, it is important to properly isolate, diagnose and treat them. This article describes modern methods of diagnostics, including spirometry, bronchoprovocation tests, allergy tests, and methods to distinguish between these two conditions by identifying inflammatory markers. Patients will also be provided with detailed information on effective approaches and treatment strategies. The results of the study show that it is possible to significantly improve the quality of life of patients by using the correct diagnosis and appropriate therapy methods.